Semantic people tagging and ontology maturing: an enterprise social media approach to competence management. (1st January 2012) - Braun, Simone; Kunzmann, Christine; Schmidt, Andreas P.
Semantic people tagging is an Enterprise 2.0-style approach to making expertise and individual capabilities transparent. By combining it with a collaborative ontology editor and thus the possibility to construct a shared vocabulary and understanding, it can be a supplement for cumbersome competence management, or expert finder solutions, which lack acceptance among employees, and suffer from outdated data. It gives human resources a timely overview of available and required competencies based on peer reviews and actual usage. However, it also needs to be tailored to the cultural characteristics of a specific company. Therefore, we have developed a design framework for semantic people tagging. We want to present the general approach based on the ontology maturing concept of gradual formalisation and its implementation based on a social semantic bookmarking system. Focus group interviews with HR experts have further have yielded insights into the wider context and validated the concept. The system has been introduced and evaluated at a company for career advising, and is being rolled out to additional contexts.